2022
DOI: 10.1136/bmjopen-2022-064538
|View full text |Cite
|
Sign up to set email alerts
|

EPI-ASTHMA study protocol: a population-based multicentre stepwise study on the prevalence and characterisation of patients with asthma according to disease severity in Portugal

Abstract: IntroductionIn Portugal as in other countries, data on the epidemiology of asthma are mainly grounded in questionnaire studies. Additionally, the detailed characterisation of asthma in terms of disease severity, control and phenotypes remain scarce. Studies assessing the prevalence of asthma and its subgroups using accurate methods are needed. This study aims to determine the prevalence of asthma, difficult-to-treat asthma and severe asthma, and to evaluate sociodemographic and clinical characteristics of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…EPI-ASTHMA used a stepwise approach, sequentially comprising 4 stages, that has been described in detail elsewhere. 15 A brief summary of each stage is provided below and Table 1 specifies the data collected at each stage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EPI-ASTHMA used a stepwise approach, sequentially comprising 4 stages, that has been described in detail elsewhere. 15 A brief summary of each stage is provided below and Table 1 specifies the data collected at each stage.…”
Section: Methodsmentioning
confidence: 99%
“…The minimum initial sample size estimation for this pilot study was found to be 1316 participants based on an estimated prevalence described elsewhere. 15 The characteristics of participants were described with mean and standard deviation (SD) for normally distributed variables; for skewed distributions we used median and interquartile range (IQR; range from 25th to 75th percentile). Categorical variables were described with absolute frequencies, proportions and 95% confidence intervals (95% CI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation